Distinguishing Features of Teacher Image and Faculty Member's Image: Comparative Study - Mynbayeva, Aigerim; Yessenova, Kamchat (International Review of Management and Marketing, 2016)
Educator's image has become a necessary attribute of professional activity in the modern postindustrial society. There has been a lot of scientific research on political image. Personal image contributes to professional's competitiveness in the labour market, especially in the modern globalising world. On the one hand, image encourages personal promotion and success in the labour market. On the other hand, it encourages personal self-fulfillment through recognition by the society and personal success. The internationalisation of higher education implying universities' participation in various rankings lead to the situation when research on the image of the university, involving educators' vision of the one, becomes quite topical. The aim of the article is to summarise the approaches to building teacher image and to compare characteristics of teacher image and faculty member's image. The authors analysed the approaches to developing theories of pedagogical image, compared teacher image and faculty member's image based on questionnaire survey, offered recommendations for educators. The following functions of image were summarised and analysed: social and informational, nurturing, professional, motivational, and developing. The components of pedagogical image were revealed: the core of pedagogical image (self-concept; internal image - axiological (value-concsious) image, system of values, personality traits; charisma, professionalism and pedagogical competency); external image: visual image – walking manner; clothes; hairstyle; way of moving; makeup for women; accessories; perfumery; verbal behavior: voice; mood; non-verbal behavior: manner; gestures; facial expressions; information image. 121 teachers participated in practical part of the research including 85 school teachers and 36 university faculty members from Kazakhstan. According to the respondents' self-assessment 71,8 percent of school teachers and 66,7 percent of faculty members noted that their actual and ideal images fail to meet. However, only less than half of school teachers (27,1 percent) and about one third of faculty members (22,9 percent) wanted to change it. School teachers and faculty members expressed their interest and positive reaction to the idea of organizing “A workshop on pedagogical image”. Most of them would like the workshop to be organized at schools (40 percent) and universities (47,92 percent), as well as at Advanced training institutes (48,53 percent of school teachers and 43,75 percent of faculty members). Keywords: pedagogical image, imageology, teacher's authority. JEL Classifications: I20; I23; I26